Chapter I Conti erariali dei feudi nella I serie delle Dipendenze della Sommaria dell'Archivio di Stato di Napoli (XV secolo): per un nuovo inventario ragionato - RIVERA MAGOS, Victor (Reti Medievali E-Book, 2021)
In this paper we present the results obtained from the systematic investigation of the sub-series 'Conti erariali dei feudi' of the fund 'Dipendenze della Sommaria' preserved in the State Ar- chives of Naples. A reasoned analytical inventory is proposed, limited to the documentation re- lating to the period between 1421 and 1500, for a count of 58 envelopes and 212 dossiers. This is fiscal documentation that has flowed into the Archive of the Camera della Sommaria following the deliveries by the provincial administrators required to submit their work to the audit of the rational of the king, but also as a result of traumas and confiscations on fiefs by the sovereign.